Living Theology of the Punggahan Tradition in the Javanese Ethnic of Paya Lombang Tebing Tinggi - Dini Apriasti; Nunu Burhanuddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study entitled “Living Theology in the Punggahan Tradition among the Javanese Ethnic Community in Paya Lombang, Tebing Tinggi” aims to analyze the Punggahan tradition as both a socio-cultural-religious phenomenon and a manifestation of living theology. This research employs a qualitative approach with a phenomenological method through observation, interviews, and documentation involving religious leaders, community figures, and members of the Javanese ethnic group. The findings indicate that the Punggahan tradition serves not only as a ritual for welcoming Ramadan but also as a space for integrating social, cultural, and religious values in everyday life. From a socio-cultural-religious perspective, this tradition plays an important role in strengthening social solidarity, togetherness, and harmonious relationships within the community through activities such as communal prayers, grave visits, shared meals, flower bathing rituals, and mutual forgiveness. From the perspective of living theology, the Punggahan tradition demonstrates how Islamic theological values such as gratitude, monotheism (tawhid), Islamic brotherhood (ukhuwah Islamiyah), self-purification, charity, and prayer are lived and practiced in a concrete and contextual way. These values are not only understood conceptually but are embodied in daily communal practices passed down from generation to generation. Thus, it can be concluded that the Punggahan tradition represents a form of harmony between religion and culture, serving not only a social function but also standing as a real manifestation of living theology in the life of the Javanese community.